Color changing and behavioral context in the Amazonian dwarf cichlid Apistogramma hippolytae (Perciformes) - Rodrigues, Raoni Rosa (2009)
Animal coloration has many functions, and fishes are noted among vertebrates for presenting a wide variety of color patterns. Although in marine fishes the relationship between body coloration and behavioral context is well documented, there's not much information about freshwater fishes. Here we describe color patterns displayed by the dwarf cichlid Apistogramma hippolytae and suggest that these patterns are dependent on different social and behavioral settings. Field observations were conducted underwater in a pond in Central Amazonia, Brazil. We recorded six body coloration patterns related to seven different kinds of behavioral activities: foraging, resting, reproductive and agonistic displays, aggression (attacking and fleeing) and parental care. Changes in coloration occur rapidly and take only a few seconds. Females on parental care exhibited a unique pattern that are more persistent and probably manifests more slowly. In the shallow and clear waters of the natural environment of this dwarf cichlid, color communication seems to constitute an efficient way to display information about individual mood, social status and reproductive readiness, contributing to minimize loss of energy in unnecessary interactions. © 2009 Sociedade Brasileira de Ictiologia.